2021
DOI: 10.3390/jmse9101102
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Scour Beneath Pipelines Subjected to an Oscillatory Flow Condition

Abstract: The present study carries out two-dimensional numerical simulations to investigate scour beneath a single pipeline and piggyback pipelines subjected to an oscillatory flow condition at a Keulegan–Carpenter (KC) number of 11 using SedFoam (an open-source, multi-dimensional Eulerian two-phase solver for sediment transport based on OpenFOAM). The turbulence flow is resolved using the two-phase modified k−ω 2006 model. The particle stresses due to the binary collisions and enduring contacts among the sediments are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The two-phase model for simulating sheet flows in the open-source CFD software OpenFOAM is referred to as SedFOAM [96][97][98]. SedFOM has achieved accurate prediction of scour around subsea pipelines [99][100][101]. However, the two-phase models have not been used in cases with complex geometries as much as the one-phase sediment transport rate models, mainly due to their slower computational speed.…”
Section: Two-phase Modelmentioning
confidence: 99%
“…The two-phase model for simulating sheet flows in the open-source CFD software OpenFOAM is referred to as SedFOAM [96][97][98]. SedFOM has achieved accurate prediction of scour around subsea pipelines [99][100][101]. However, the two-phase models have not been used in cases with complex geometries as much as the one-phase sediment transport rate models, mainly due to their slower computational speed.…”
Section: Two-phase Modelmentioning
confidence: 99%
“…(3) Submarine Pipelines, Underwater Tunnel Linings, and Subsea Shuttle Tanker Two-dimensional numerical simulations were performed in [9] to investigate scour beneath a single pipeline and piggyback pipelines subjected to an oscillatory flow condition at a Keulegan-Carpenter (KC) number of 11 using an open-source SedFoam. The turbulence flow was resolved using the two-phase modified k-ω 2006 model, and the particle stresses due to the binary collisions and enduring contacts among the sediments were modeled using the rheology model of granular flow.…”
Section: (1) Pile or Monopile Foundationsmentioning
confidence: 99%
“…The numerical results showed that the maximum vibration amplitude of the pipeline could reach about 1.2 times diameter, and the maximum scour depth occurred on the wake side of the vibrating pipeline. In 2021, Huang [16] carried out two-dimensional numerical simulations to investigate the scour beneath a single pipeline and piggyback pipelines subjected to an oscillatory flow condition at a KC number of 11 and captured typical steady-streaming structures around the pipelines due to the oscillatory flow condition. In 2021, Cui [17] investigated the characteristics of the riverbed scour profile for a pipeline buried at different depths under the condition of riverbed sediments with different particle sizes.…”
Section: Introductionmentioning
confidence: 99%